Prevalence of specific learning disability among schoolchildren between 8 and 12 years (Indian Journal of Child Health, 2018)
Background: Specific learning disability (SLD) is known to cause a great amount of psychological and mental stress to the children and their parents. Objectives: To find out the prevalence of SLD among children in Gwalior and to find out the risk factors associated with SLD. Method: This cross-sectional study was conducted between 2016 and 2017 in two government and two private schools of Gwalior. A total of 800 students from the 3rd to 6th standard were included in the study. The details of every student were filled in a pro forma which included their academic performance. Based on this, last 10% of the low-performing students from each class were recruited and they were subjected to visual, hearing, IQ assessment, and NIMHANS index for SLD. Results: A total of 23 students were identified as having SLD, with a prevalence of 2.87%. The most common type was combined type (dyslexia and dyscalculia). The prevalence of arithmetic disability was found to be around 2.25%, reading disability was 2.5%, and that of writing disability was around 1.37%. The mean age of students diagnosed as SLD was 9.8. Among the learning-disabled students, 19 students (82%) were having only one sibling. SLD was diagnosed mostly in class IV students (p=0.023). Among SLD students, a history of prematurity was found in 11 students (48%), low birth weight in 13 students (57%), and head trauma in 13 students (57%) with SLD. Among SLD students, 7 were having attention-deficit hyperactivity disorder (ADHD). No students were identified as having ADHD in the remaining students and it was highly significant (p<0.001). Conclusion: The prevalence of SLD was 2.87%, with the most common type being combined type. The antenatal risk factors associated with SLD were prematurity, low birth weight, and a history of head trauma. The most common comorbid condition associated with SLD was attention-deficit hyperactivity disorder.